The Effect of Perceptions of Undergraduate Accounting Students about the Social Values Againts on Interest Choosing an Career As A Public Accountant (Study on Undergraduate Accounting Students of Mataram University) - Muhamad Yunus; Bambang; Iman Waskito (Formosa Journal of Multidisciplinary Research, 2023)
This research aimed at finding out and to analyze the effect of Perceptions of Undergraduate Accounting Students About the Social Values Againts Interest Choosing an Career as a Public Accountant (Study on Undergraduate Accounting Students of Mataram University). This research uses Expectancy Theory and Need Theory as a theoritical basis. This research used primary data with a quantitative methode. The population in this research were accounting students program period 2018, 2019 and 2020 as many as 726 people and got the sample as many as 153 people. The sample collection technique used is purposive sampling with data collection methode is a questionnaire. The data analysis technique used in this research is descriptive statistics and path analysis. The result showed that Material Values and Spiritual Values had a significant effect on undergraduate accounting students perceptions on the interest choosing an career as a Auditors, while Vital Values had does not significant effect. Perceptions of Undergraduate Accounting Students had a mediation significantly of the effect between Material Values and Spiritual Values on interest choosing an career as an Auditors, while Vital Values had does not madiate significantly.